The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1055/s-0037-1612600
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Outcome after Successful Mechanical Thrombectomy in Patients with Acute Anterior Circulation Stroke

Abstract: Successful revascularization is one of the main predictors of a favorable clinical outcome after mechanical thrombectomy. However, even if mechanical thrombectomy is successful, some patients have a poor clinical outcome. This study aimed to investigate the clinical, imaging, and procedural factors that are predictive of poor clinical outcomes despite successful revascularization after mechanical thrombectomy in patients with acute anterior circulation stroke. The authors evaluated 69 consecutive patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In line with our findings, other studies report no significantly increased rates of sICH in EVT patients on anticoagulation [23,27,28] . A recent study found higher rates of sICH in patients on warfarin but not on NOACs, when compared to non-anticoagulated cases [29] . A previous study reported no difference in sICH rates between warfarin and NOACs, but the number of patients on a NOAC was small [23] .…”
Section: Discussionmentioning
confidence: 92%
“…In line with our findings, other studies report no significantly increased rates of sICH in EVT patients on anticoagulation [23,27,28] . A recent study found higher rates of sICH in patients on warfarin but not on NOACs, when compared to non-anticoagulated cases [29] . A previous study reported no difference in sICH rates between warfarin and NOACs, but the number of patients on a NOAC was small [23] .…”
Section: Discussionmentioning
confidence: 92%
“…1 Factors such as age, National Institutes of Health Stroke Scale (NIHSS) score at baseline, and Alberta Stroke Program Early CT Score (ASPECTS) are associated with poor outcome after successful reperfusion. [2][3][4][5] A better understanding of the key determinants of poor recovery despite successful reperfusion after EVT could guide researchers and physicians in the development of new treatments to further improve outcomes. Therefore, we aimed to quantify the importance of predictors of poor functional outcome despite successful reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive analysis of thirty-nine studies [8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]51], comprising a total of 11,700 patients, was conducted to assess the pooled prevalence of FR in AIS patients (Figure 2). The meta-analysis revealed an estimated pooled prevalence of 51%, with a range between 48% and 54% (ES 51%; 95% CI 48-54%; z = 47.66; p < 0.001) (Table 2 and Figure 2).…”
Section: Prevalence Of Futile Recanalizationmentioning
confidence: 99%
“…Twenty-two studies [11,15,17,19,[21][22][23][24][25]28,[30][31][32][33][34]39,40,[42][43][44][45]51], with a cumulative cohort of 5455 patients, examined the pooled prevalence of FR in AIS patients through retrospective studies (Figure 2). The meta-analysis indicated an estimated pooled prevalence of 51%, with a range from 46% to 56% (ES 51%; 95% CI 46-56%; z = 31.07; p < 0.001) (Table 4).…”
Section: Prevalence Of Fr In Retrospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation